Students Ways of Thinking on Geometry - Resy Nirawati; Darhim Darhim; Siti Fatimah; Dadang Juandi (Didaktik Matematika, 2022)
Ways of Thinking (WoT) is a fundamental ability that is part of the mental act that students must learn to solve geometry problems. The purpose of this research was to describe how WoT is used to solve geometry problems. This research used the descriptive qualitative methodology with a holistic case study design and data collection techniques such as tests, interviews, observation, documentation, and triangulation. The subjects in this research were 35 fourth-grade students from Sambas Regency Public Elementary Schools, Indonesia. The research focused on three students with varying levels of cognitive abilities: low, medium, and high.The results showed that students with high, medium, and low cognitive capabilities performed mental acts with the corresponding WoT. Students with high, medium and low cognitive capabilities were more likely to work on questions that required interpretation. Besides, it also revealed that errors committed students were learning errors, reading errors, careless errors, conceptual errors, and procedure errors. The implementation of WoT on the topic of geometry can be utilized as an alternate reference for mathematics teachers when developing teaching materials for mathematics learning to increase studentss' mathematical knowledge.